Edukasi Aksi Makan Bergizi Sehat Siswa Sekolah Dasar sebagai Upaya Pencegahan Stunting pada Siswa Di SDN Oebali Desa Bone Kabupaten Kupang - Johny Salmun; Sintha Purimahua; Marni Marni; Ribka Limbu (GOTAVA, 2024)
Community service activities carried out at the Bone Nekamese Village Elementary School, Kupang Regency aim to increase public awareness, in this case children, of the importance of nutrition to reduce the increase in stunting rates, especially in Kupang Regency. The activities carried out include nutritional education, providing medical assistance to the school, in the form of blood supplement tablets.